2018
DOI: 10.4184/asj.2018.12.3.518
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Correlation between Muscle Damage and Oswestry Disability Index Score after Open Lumbar Surgery: Does Open Surgery Reduces Functional Ability?

Abstract: Study DesignSingle-surgeon, single-center prospective study with prospective data collection.PurposeTo clinically evaluate muscle damage after open lumbar surgery and its relationship to functional activity and to validatethe improvement in function as indicated by improved Oswestry Disability Index (ODI) score despite muscle damage.Overview of LiteratureFew studies have analyzed the functional loss and recovery pattern of muscles after open lumbar surgery.MethodsThe study included 30 patients who underwent op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…23,24 A recent study reported significant decrease of 1.1% to 4.2% in thigh muscle volume and 1.0% to 3.4% in quadriceps within 5 days after surgery. 25 Tandon et al 26 showed significant damage to the lumbar paraspinal muscles (a reduction in the CSA and denervation) after lumbar fusion surgery.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 A recent study reported significant decrease of 1.1% to 4.2% in thigh muscle volume and 1.0% to 3.4% in quadriceps within 5 days after surgery. 25 Tandon et al 26 showed significant damage to the lumbar paraspinal muscles (a reduction in the CSA and denervation) after lumbar fusion surgery.…”
Section: Discussionmentioning
confidence: 99%
“…For evaluating soft tissue trauma post-operatively, most studies used imaging studies (CT or MRI) to evaluate the morphology of the para-spinal muscle, and revealed that MIS can decrease post-operative muscle atrophy as compared with COS. 18 - 20 However, Urrutia et al suggested that single-level fat signal fractions and cross-sectional area are not representative of the whole lumbar spine. 21 Surface EMG is an objective and effective tool for evaluating back muscle function.…”
Section: Discussionmentioning
confidence: 99%
“…During the posterior lumbar surgery exposure process, it is inevitable that paravertebral muscles will be stripped and damaged [ 34 ]. Postoperative lumbar MRI shows that paravertebral muscles have different degrees of injury [ 35 ], accompanied by low back pain and dysfunction [ 36 ]. However, minimally invasive surgical methods can significantly reduce paravertebral muscle atrophy.…”
Section: Factors Of Multifidus Injurymentioning
confidence: 99%